Anhaltende postpartale Ängste: psychosoziale Risikofaktoren sind am bedeutsamsten (PPmP - Psychotherapie · Psychosomatik · Medizinische Psychologie, 2017)
Dennis CL et al. Identifying women at risk for sustained postpartum anxiety. J Affect Disord 2017; 213: 131–137